KUANTIFIKASI PENGARUH TERMINAL BAYANGAN TERHADAP KINERJA SIMPANG TAK BERSINYAL BERBASIS PKJI 2023 - Ridwan Rinaldo Loe; Andi Kumalawati; Remigildus Cornelis; Alvin Alfredo Bara4 (Racic : Rab Construction Research, 2026)
Informal terminals are unofficial public transport stopping points that generate side friction and may degrade the performance of urban unsignalized intersections. This study evaluates the performance of the Sikumana four-leg unsignalized intersection in Kupang City and quantifies performance changes caused by informal terminal activities. A quantitative descriptive case-study approach was applied using the Indonesian Highway Capacity Guidelines (PKJI) 2023, with level of service classified according to HCM 2000. Primary data were collected through surveys of geometry, traffic volume, speed, side friction, and informal terminal activities over seven days during three peak periods. Four scenarios were analyzed: existing 2025 with the informal terminal, 2025 without it, and 2030 projections with and without it. At the peak hour (Monday, 11 August 2025, 17.00–18.00), traffic flow reached 2,765.60 pcu/hour against a capacity of 2,701.10 pcu/hour, yielding a degree of saturation of 1.024, delay of 20.184 sec/pcu, queue probability of 42.15–83.59%, and LoS C. Removing the informal terminal increased capacity by 2.15%, reduced the degree of saturation to 1.002 and delay to 19.160 sec/pcu, yet the intersection remained oversaturated at LoS C. The 2030 projection shows LoS E in both scenarios; therefore, informal terminal management should be combined with staged traffic management.